2001
DOI: 10.1093/jjco/hye008
|View full text |Cite
|
Sign up to set email alerts
|

Prospective and Randomized Comparison of Combined Androgen Blockade Versus Combination with Oral UFT as an Initial Treatment for Prostate Cancer

Abstract: This endocrine chemotherapy was confirmed to be tolerable and significantly effective in the delay of disease progression, which leads to longer survival in patients with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…28 -30,40,43 Others were limited in many respects, including presentation of results and missing data reporting. 25,34,38,48,49 Prostate carcinoma patients are usually older than the general cancer population. Thus, the treatment is often debilitating without significantly prolonging survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 -30,40,43 Others were limited in many respects, including presentation of results and missing data reporting. 25,34,38,48,49 Prostate carcinoma patients are usually older than the general cancer population. Thus, the treatment is often debilitating without significantly prolonging survival.…”
Section: Discussionmentioning
confidence: 99%
“…32 Nevertheless, some trials reported limited information about the nature of the HRQOL measure used while others created ad hoc measures without giving any information about the developmental process. 25,38,48,49 …”
Section: Hrqol Assessment Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…This combines the DPD inhibitor uracil and tegafur, which is converted to 5-FU in the liver, at a 4:1 molecular ratio, and has been used for the treatment of colon, lung, breast, gastric and prostate cancers, among others (48)(49)(50)(51)(52)(53). In patients with untreated advanced prostate cancer, combined therapy with UFT and first-line MAB was reported to be tolerable, and effectively delayed the progression to androgen-independence (54)(55)(56). At the 2010 American Society of Clinical Oncology (ASCO) annual meeting, we reported that combination therapy with uft and second-line MAB was more effective than second-line MAB alone in a study of 53 patients with HRPC (2010 ASCO Annual Meeting abs.…”
Section: Discussionmentioning
confidence: 99%
“…Kuriyama et al [23] reported on the use of daily uracil and tegafur (UFT; in a molar ratio of 4:1) in combination with orchiectomy and DES compared with orchiectomy and DES treatment alone. Progression-free survival improvement on addition of UFT was not quite statistically signifi cant for the whole cohort (51.…”
Section: Preclinical Evaluation Of Taxanes Alone or In Combination Wimentioning
confidence: 99%